Andrushchenko M.І., Ph.D., Osіpov M.Y., Ph.D., Kulikovsky R.A., Ph.D., Kapustіan О.YЕ., Magda Е.S. Akrytova T.О. Designing of the technology of restoration and strengthening of the crankshaft knee-lever presses. Part 2: Technological process and special e - Андрущенко, М. І.; Осіпов, М. Ю.; Куликовський, Р. А.; Капустян, О. Є.; Акритова, Т. О. (Problems of Tribology, 2018)
A comparative analysis of the methods for restoring worn shaft working elements has shown that the best option for restoring the surfaces of the crankpin and seats is a wide-layer surfacing with a cold rolled strip under the flux, and it is advisable to weld the keyways with a wire of continuous cross section in shielding gases. The parameters of recovery regimes for worn shaft working elements are substantiated. The main ones are: the arc voltage is 30-32 V, the arc current is 650 ± 20 A, the deposition rate is 0.5 cm/s. A special equipment is proposed on which it is possible to weld a crank neck and seating places. A technological process route is developed. The technical and economic calculations have shown that when restoring and strengthening even one shaft, the economic effect can reach hundreds of thousands of hryvnias.